PENGARUH BELIEF CONTROL SYSTEM DAN BOUNDARY CONTROL SYSTEM TERHADAP CUSTOMER ORIENTED MEASURE DENGAN MODERASI EMPLOYEE ORIENTED MEASURE - Yuliana Yuliana Yuliana; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this study was to know the influence of belief and boundary control systems on customer oriented measure with moderation of employee oriented system. The population used in this study was 35 public companies which operated in Indonesia, with a sample 104 people. The analysis technique used in this study was a partial least square. The result of the study showed that the belief control system and boundary control system had a significant positive affect on customer oriented measure, belief and boundary control system had a significant positive affect on customer oriented measure with the moderation of employee control system.